2017
DOI: 10.1016/j.otsr.2016.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Effect of warming bupivacaine 0.5% on ultrasound-guided axillary plexus block. Randomized prospective double-blind study

Abstract: Warming bupivacaine 0.5% to 37°C accelerated onset of sensory and motor block and extended action duration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Our study has revealed that the administration of 0.5% ropivacaine at a temperature of 30℃ can signi cantly speed up the onset time for both sensory and motor block in subgluteal sciatic nerve, which is consistent with previous researches on brachial plexus block [22][23][24]. Compared to brachial plexus blocks, warming local anesthetics for the subgluteal sciatic nerve holds greater clinical signi cance due to its thicker construction and slower onset time.…”
Section: Discussionsupporting
confidence: 90%
“…Our study has revealed that the administration of 0.5% ropivacaine at a temperature of 30℃ can signi cantly speed up the onset time for both sensory and motor block in subgluteal sciatic nerve, which is consistent with previous researches on brachial plexus block [22][23][24]. Compared to brachial plexus blocks, warming local anesthetics for the subgluteal sciatic nerve holds greater clinical signi cance due to its thicker construction and slower onset time.…”
Section: Discussionsupporting
confidence: 90%
“…7, 13 According to Trabelsi et al, heating increases the diffusion capacity of local anaesthetic, thereby resulting in early onset of the action. 14 The duration of sensory blockade and the median highest sensory level has shown comparable results without any significance. Twosegment regression and the motor characteristics of the subarachnoid block were comparable among both groups.…”
Section: Figure 4 -Number Of Patients With Hypotension Episodes In Ea...mentioning
confidence: 91%
“…In the literature, few studies focused on the effect of warming local anesthetics on peripheral nerve block [ 6 ]. To our knowledge, they were only limited to brachial plexus block.…”
Section: Introductionmentioning
confidence: 99%